2013
DOI: 10.1016/j.pmcj.2013.07.014
|View full text |Cite
|
Sign up to set email alerts
|

From big smartphone data to worldwide research: The Mobile Data Challenge

Abstract: This paper presents an overview of the Mobile Data Challenge (MDC), a large-scale research initiative aimed at generating innovations around smartphone-based research, as well as community-based evaluation of mobile data analysis methodologies. First, we review the Lausanne Data Collection Campaign (LDCC) -an initiative to collect unique, longitudinal smartphone data set for the MDC. Then, we introduce the Open and Dedicated Tracks of the MDC; describe the specific data sets used in each of them; discuss the k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
60
0
7

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(71 citation statements)
references
References 23 publications
0
60
0
7
Order By: Relevance
“…Prior work has applied supervised learning to a small sample of smartphone sensor and usage data and achieved good performance at predicting marital status (37,53). {{,##,kk Related research has also demonstrated the feasibility of inferring relationship status from an online social network graph (38).…”
Section: Resultsmentioning
confidence: 99%
“…Prior work has applied supervised learning to a small sample of smartphone sensor and usage data and achieved good performance at predicting marital status (37,53). {{,##,kk Related research has also demonstrated the feasibility of inferring relationship status from an online social network graph (38).…”
Section: Resultsmentioning
confidence: 99%
“…Due to lack of freely available data sets, a highly convenient Android based app for tracking of users' behavior, environment and ground truth annotation was developed [Kiukkonen et al, 2010, Laurila et al, 2013, Yu Zheng, 2011. A sizeable amount of valid data was collected and submitted by 19 participants over a time span of 183 days.…”
Section: Resultsmentioning
confidence: 99%
“…Hence, the classification as either one of them lies solely in context of visit. Due to these circumstances the MDC treated these two place types as one [Laurila et al, 2013]. The relative high precision value of 0.867 suggests that distinguishing features exist, since nightlife is classified correctly, both place types can still be treated separately.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The CloudAware has context adaptation feature to select appropriate connection selection and offload timing, by means of its history based prediction of user future movement, available c 2018 Information Processing Society of Japan bandwidth, and the execution time of an task. For realistic evaluation, they use Nokia Mobile Data Challenge (MDC) dataset [65] that contains activity records of data from smartphones of almost 200 volunteers over 18 months in Lausanne area, such as smartphone location, Cellular/WiFi connection status, device battery level, application usage, and so on. Evaluation is done in simulation in which each application tasks are judged either success or failure; the task may fail because of various reason such that the device battery runs out, the nearby MEC server is overloaded, or connection is lost by user's movement.…”
Section: Architectural Studiesmentioning
confidence: 99%